Implementing English-medium instruction (EMI) in China: teachers' practices and perceptions, and students' learning motivation and needs - Jiang, Li; Zhang, Lawrence Jun; May, Stephen (International journal of bilingual education and bilingualism, 2019)
This paper reports on a classroom-based investigation into a tertiary English-medium instruction (EMI) programme in China, with a focus on subject teachers' perceptions and practices in EMI and students' motivation and needs in English learning. Given a lacuna in existing EMI research, it examined how EMI instruction was delivered by subject teachers and how English learning should be facilitated through adjunct ESP courses when participants' English proficiency was inadequate. Data were obtained from nine classroom observations, three post-observation interviews and a questionnaire survey. Findings show that effective instruction was maintained via deploying pragmatic strategies, yet the goal of promoting English attainment was underachieved, as language teaching was not overtly heeded. Subject teachers' perceptions of EMI undermined prospective students' linguistic gains. The immediate educational context also contributed to students' English learning motivation and needs. Our findings suggest increasing access to ESP provision that is fine-tuned to the language issues in genuine EMI classrooms is crucial. Collaboration between subject and language specialists is beneficial to students' learning of both the subject knowledge and the language skills. ESP practitioners thus need to consider students' communicative needs in their disciplines and address the limitations of the current EMI practices in tertiary education in China.